2013
DOI: 10.1159/000347050
|View full text |Cite
|
Sign up to set email alerts
|

A Defined-Multispecies Microbial Model for Studying Enamel Caries Development

Abstract: The aims of this study were to describe and validate an in vitro multispecies microbial biofilm model for caries development by evaluating the effects of varying medium concentration of sucrose (0.5 and 1.0%) and fluoride (0.4, 0.8 and 1.0 ppm F) in study 1, and calcium (1.0 and 2.0 mM Ca) in study 2. Defined-multispecies biofilms, formed by Lactobacillus casei, Streptococcus mutans, S. salivarius and S. sanguinis, were grown on the surface of salivary-pellicle-coated enamel slabs, with known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 79 publications
3
39
1
2
Order By: Relevance
“…Carbohydrates present in the STGM might not be high enough to result in significant levels of acid production to enable the selection of acidogenic species and ultimately create a cariogenic state. However, based on the assertion that adjunct sucrose is sufficient for this process [Pratten et al, 2000;Aires et al, 2006;Arthur et al, 2013], the reduction in sucrose concentration which occurs with the effect of mixing STGM and sucrose solution in the CF condition may have some influence on the lesions that are created. In effect, a 50-m M sucrose challenge in the FF condition would equate to approximately a 25-m M challenge in the CF condition.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrates present in the STGM might not be high enough to result in significant levels of acid production to enable the selection of acidogenic species and ultimately create a cariogenic state. However, based on the assertion that adjunct sucrose is sufficient for this process [Pratten et al, 2000;Aires et al, 2006;Arthur et al, 2013], the reduction in sucrose concentration which occurs with the effect of mixing STGM and sucrose solution in the CF condition may have some influence on the lesions that are created. In effect, a 50-m M sucrose challenge in the FF condition would equate to approximately a 25-m M challenge in the CF condition.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory biofilm models have been shown to mimic the oral environment and reproduce dental biofilm mediated events in vitro (Sissons 1997;Tang et al 2003;McBain 2009) and have been used for studies related to the aetiology and treatment of dental caries van de Sande et al 2011;Arthur et al 2013). When complex microbial communities originating from the natural ecosystem (microcosm) (Wimpenny 1997) are used in these models, the microbial complexity and heterogeneity of the initial inoculum are maintained at some level, allowing the study of variables related to dental caries in a controlled environment (Filoche et al 2008;McBain 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the fluoride concentration used by these cited studies was higher than what was used in the present study, the previous data might contribute to understanding the predominance of lactobacilli in the biofilm. On the other hand, it has been shown that an increased concentration of fluoride from 0.2 to 1.0 ppm during biofilm growth was able to decrease the viability of L. casei in a multispecies biofilm model [44]. Within this same range of fluoride concentration, the lowest counts of S. mutans were found only in the presence of 0.2 ppmF and no statistical difference was found for those counts under fluoride concentrations up to 1.0 ppmF [44].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that an increased concentration of fluoride from 0.2 to 1.0 ppm during biofilm growth was able to decrease the viability of L. casei in a multispecies biofilm model [44]. Within this same range of fluoride concentration, the lowest counts of S. mutans were found only in the presence of 0.2 ppmF and no statistical difference was found for those counts under fluoride concentrations up to 1.0 ppmF [44]. Using the same microbial composition used in this present study, Fontana et al [20] were able to find expressive counts of S. mutans on biofilms even after 8 d of biofilm growth.…”
Section: Discussionmentioning
confidence: 99%